Case management services for jobseekers. International comparisons: Sweden, the Netherlands and the United Kingdom - Georges, Nathalie; Grivel, Nicolas; Méda, Dominique (Noisy-le-Grand, 2009)
"In most European countries, there are reforms in progress aimed at individualising the journey to return to work so as to guide each person in function to their needs. However, the definition of the nature and degree of this case management has not been stabilised. This study’s main goal is to clarify the content of case management: in function to the specificities of each system, how are the case management processes organised? Who are the service providers and beneficiaries? And what services are proposed to the latter? The study examines the case management in three countries: Sweden, the Netherlands and the United Kingdom, all presented as models consecutive to employment policies and structural reforms carried out since the 1990s having encouraging results in terms of unemployment rates. This diversity of institutional organisations enables to test the hypothesis of a progressive convergence of approaches touching upon the notion of individualised case management and the recourse to comparable services in function to the jobseekers’ profiles. The three countries visited have comparable evolutions concerning their approach to employment policies, although each of them conserves some of their specificities linked to their history and their social and political preferences. The study underlines the common trends which are related to institutional reforms, guidance and individualised tracks and short services aiming for a rapid return to employment.